Respuesta :
For this case, what we must do is equal the function to zero:
b ^ 2 - 75 = 0
From here, we clear the value of b. We have then:
b = + / - root (75)
We rewrite:
b = + / - root (3 * 25)
b = + / - 5 * root (3)
So, the roots are:
b1 = 5 * root (3)
b2 = -5 * root (3)
Answer:
The roots of the quadratic function are:
b1 = 5 * root (3)
b2 = -5 * root (3)
b ^ 2 - 75 = 0
From here, we clear the value of b. We have then:
b = + / - root (75)
We rewrite:
b = + / - root (3 * 25)
b = + / - 5 * root (3)
So, the roots are:
b1 = 5 * root (3)
b2 = -5 * root (3)
Answer:
The roots of the quadratic function are:
b1 = 5 * root (3)
b2 = -5 * root (3)
Answer:
the ANSWER IS A) AND B) ON EDGE I JUST TOOK THE TEST
Step-by-step explanation:
HOPE THIS HELPED